Legal Policy Impact on Indonesia's Geothermal Industry Development: FDI Cooperation and NDC - Rahmawanti, Hanifah Humaira; Meliala, Aurora Jillena (Journal of Law, Politic and Humanities, 2024)
Geothermal significantly contributes to the state's energy industry development as a widely available low-carbon, sustainable, and strategic resource. As Indonesia is committed to achieving NZE 2060, renewable energy development is being conducted massively. Seeking Indonesia's geothermal energy potential, several regulations, policies, and schemes are implemented, including investment schemes, as financing plays a vital role in the industry's development. However, establishing a seamless procurement is highly dependent on national law regulations which govern the financing, procurement, and utilizations up to investors benefits. This article identifies international and national regulations on FDI, business schemes, and its alignment with INDC strategic programs, demonstrating Indonesia's commitment. It finds much room for improvement in national law regulation, especially the upcoming RE Draft Bill, as the implementation of established FDI schemes has not met the investor's favors. However, among AMS, Indonesia is the most committed country to achieving NZE. Therefore this article examines the Legal Policy Impact on Indonesia’s Geothermal Industry Development through FDI Cooperation and NDC. This article is conducted in Normative Legal Research and uses the Statutory Approach as its problem approach.